Fatal skin and pulmonary infection caused by Hormographiella aspergillata in a leukaemic patient: case report and literature overview. Issue 6 (15th May 2013) - Bojic, Marija; Willinger, Birgit; Rath, Thomas; Tobudic, Selma; Thalhammer, Florian; Böhm, Alexandra; Mitterbauer, Margit; Schulenburg, Axel; Wöhrer, Stefan; Kalhs, Peter; Rabitsch, Werner
Summary: Invasive systemic fungal infections are a major cause of morbidity and mortality in patients after hematopoietic stem cell transplantation. We report the case of a fatal infection with Hormographiella aspergillata in a patient undergoing allogenic peripheral blood stem cell transplantation for acute myeloid leukaemia.